Factors associated with adherence among individuals with diabetes mellitus: a literature review - Khuan, Lee; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2017)
Background: Diabetes Mellitus (DM) is a condition that is characterised by an increase in the blood glycaemic level due to insufficient and defective insulin action in the body. The aim of this review was to examine the factors associated with adherence among individuals with DM. Method: A literature review was conducted on published work related to the factors associated with adherence among individuals with DM by searching online databases. Results: A total of 23 published studies that focused on the adherence to anti-diabetes drugs were reviewed. Fifteen cross-sectional studies identified several factors that were significantly associated with adherence, such as gender female (n=5), age (n=2), educational level (n=6), financial status (n=4), and knowledge or information about diabetes (n=4). Qualitative studies reported that family support and system-level facilitators were associated with adherence to the management of diabetes. Conclusion: It is suggested that diabetes education plays an important role in adherence. Health care professional should focus on the educational interventions to increase adherence to treatment.